Remoxipride: pharmacokinetics and effect on plasma prolactin. - Movin-Osswald, G (1991)
1. The pharmacokinetics of remoxipride, a new neuroleptic, were investigated in 15 healthy subjects after an intravenous infusion of 50 mg, an intramuscular injection of 100 mg and after administration of two immediate release capsules (A and B), each of 100 mg, in a cross-over study. The effect of the different remoxipride formulations on plasma prolactin concentrations was also studied. 2. The volume of distribution of remoxipride was 0.65 +/- 0.11 kg-1 (mean +/- s.d.). Total plasma clearance was 119 +/- 39 ml min-1, of which 31 +/- 13 ml min-1 was due to renal clearance. The absolute bioavailability after the i.m. and oral formulations was greater than 90%, indicating a small extent of first-pass metabolism. The mean elimination half-life was 4.8 +/- 1.4 h. The unbound fraction of remoxipride and the blood/plasma ratio were 0.19 +/- 0.03 and 0.64 +/- 0.06, respectively. 3. The transient increase in plasma prolactin was similar after all four remoxipride administrations and independent of the given dose.